1992
DOI: 10.1002/glia.440060202
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐gated currents expressed by rat microglia in culture

Abstract: Using the whole-cell patch-clamp technique, at least three types of voltage-gated currents expressed by cultured rat microglia were identified: an inward rectifier K+ current, a delayed rectifier K+ current (IK), and a Na+ current activated by depolarization. The inward rectifier conductance was activated by hyperpolarization to potentials more negative than -80 mV, depended on the external K+ concentration, and declined over time during whole cell recording, as the cell was internally dialyzed. The delayed re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 32 publications
6
66
0
Order By: Relevance
“…With peak amplitude of ϳ50 pA, they were much smaller than in neurons. Voltage-gated Na ϩ currents were expressed only in 20% of cultured rat microglial cells; the cells with ramified morphology had a higher incidence of I Na detection (471). In contrast, in human microglial cells, cultured from explants obtained during surgery on patients suffering from brain tumors, the majority of cells (30 of 32 recorded) demonstrated TTX-sensitive I Na (658).…”
Section: A Sodium Channelsmentioning
confidence: 92%
See 2 more Smart Citations
“…With peak amplitude of ϳ50 pA, they were much smaller than in neurons. Voltage-gated Na ϩ currents were expressed only in 20% of cultured rat microglial cells; the cells with ramified morphology had a higher incidence of I Na detection (471). In contrast, in human microglial cells, cultured from explants obtained during surgery on patients suffering from brain tumors, the majority of cells (30 of 32 recorded) demonstrated TTX-sensitive I Na (658).…”
Section: A Sodium Channelsmentioning
confidence: 92%
“…1) In the rat culture (471), only a subpopulation of microglial cells with a ramified morphology expressed I Na currents. It needs to be emphasized that the individually recorded cells in Korotzer's study were not identified by microglial markers and could potentially also be NG2 cells.…”
Section: A Sodium Channelsmentioning
confidence: 95%
See 1 more Smart Citation
“…In particular, expression of K þ channels in neural membranes has been related to maintenance of a variety of cellular activities, including setting the resting membrane potentials, repolarizing/hyperpolarizing cells, and buffering extracellular K þ [4,5]. As such, expression of a certain ion channel would provide a functional marker for the neural precursor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of microglia have used dissociated cultures, and Kv current expression has been highly variable (Eder, 1998): from no detectable current (Kettenmann et al, 1990Brockhaus et al, 1993) to substantial current (Korotzer and Cotman, 1992;Norenberg et al, 1994;Schlichter et al, 1996). The hypothesis that Kv current is absent from resting cells (Kettenmann et al, 1990;Brockhaus et al, 1993) and upregulated by microglial activation (Norenberg et al, 1994;Fischer et al, 1995;Visentin et al, 1995;Gebicke-Haerter et al, 1996) has been challenged because ramified microglia, widely believed to represent resting cells, express a prominent Kv current when exposed to astrocytes or astrocyte-conditioned medium (Schmidtmayer et al, 1994;Eder et al, 1997).…”
Section: Biological Implications Of Changes In Kv Expressionmentioning
confidence: 99%